Correction: Mumtaz et al. A Hybrid Framework for Detection and Analysis of Leaf Blight Using Guava Leaves Imaging. Agriculture 2023, 13, 667 - Sidrah Mumtaz; Mudassar Raza; Ofonime Dominic Okon; Saeed Ur Rehman; Adham E. Ragab; Hafiz Tayyab Rauf (Agriculture)
Affiliation Revision [...]